2013
DOI: 10.1002/grl.50379
|View full text |Cite
|
Sign up to set email alerts
|

Sustained retreat of the Pine Island Glacier

Abstract: [1] We use satellite observations to show that, between 1992 and 2011, the Pine Island Glacier hinge line retreated at a rate of 0.95 AE 0.09 km yr À1 despite a progressive steepening and shoaling of the glacier surface and bedrock slopes, respectively, which ought to impede retreat. The retreat has remained constant because the glacier terminus has thinned at an accelerating rate of 0.53 AE 0.15 m yr À2 , with comparable changes upstream. This acceleration is consistent with an intensification of ocean-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
146
2
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(158 citation statements)
references
References 41 publications
9
146
2
1
Order By: Relevance
“…Starting times of experiments computed by Joughin et al (2010) and Seroussi et al (2014) correspond to the acquisition year of the surface velocities used for inversion, 1996 and 2008, respectively. As detailed in Favier et al (2014), the starting time of their experiments corresponds to the last grounding line measurements available, i.e., completed in 2011 (Park et al, 2013). Cumulated contribution was offset to zero in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Starting times of experiments computed by Joughin et al (2010) and Seroussi et al (2014) correspond to the acquisition year of the surface velocities used for inversion, 1996 and 2008, respectively. As detailed in Favier et al (2014), the starting time of their experiments corresponds to the last grounding line measurements available, i.e., completed in 2011 (Park et al, 2013). Cumulated contribution was offset to zero in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding times are indicated by a square and a circle respectively in the upper rows. The thirdbottom row also shows the areas (shaded) separating the GL as observed in 2011 (purple line, [17]) from the relaxed model GLs, which cover 364±50 km 2 , 426±50 km 2 for Elmer/Ice, BISICLES , respectively (not shown for Úa because of the non continuous profile of the GL). The thick grey lines in the top row indicate the same area.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The thick grey lines in the top row indicate the same area. The results have been shifted to equal a null contribution at the year 2011 which is also the year of the last measured GL [17]. The corresponding offsets were estimated from the intersection between thick grey lines and changes in grounded areas from the first row in Figure 2.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…following deglaciation from the LGM (19-23 kyr). According to Larter et al (in press) the rates of change currently observed in the ASE are too high to be a simple continuation of deglaciation from the LGM as such high modern retreat rates (i.e., 0.95 ± 0.09 km yr -1 between 1992-2011; Park et al 2013) would have resulted in deglaciation of the entire continental shelf within 500 years, which is in conflict with recent marine geological data (e.g., Smith et al, 2011). There is also a growing body of geomorphological evidence that ice sheet retreat following the LGM was oscillatory with periods of rapid change punctuated by periods of relative stability (Graham et al, 2010;Jakobsson et al 2011).…”
Section: Introductionmentioning
confidence: 99%